Some ideas for reforming the community anti-dumping instrument - André Sapir (Bruegel, 2006)
André Sapir produced this short paper at the request of Commissioner Mandelson for the Expert Seminar on Trade Defence Instruments at the European Commission.
Keywords: 330; Antidumping; Außenhandelspolitik; EU-Staaten